Perilaku Konsumtif Penggemar Korean Wave di Twitter (Studi Tentang Fenomena Koleksi Photocard K-Pop) - Devina Tanliana; Lusia Savitri Setyo Utami (Koneksi, 2022)
The entertainment industry is in great demand by all circles, including South Korea, bringing K-Pop to the world stage. The success of K-Pop has produced many fans in various parts of the world, including Indonesia. K-Pop can make fans as part of consumers or customers who loyally buy their music products. In recent years, the photocard collection phenomenon has been loved by K-Pop fans. A Photocard is a selfie photo of an idol on a card and is usually included in the album as a bonus. The social media Twitter is used by K-Pop fans as an information fulfillment on the trend of this collection. Having an extensive collection of Photocards causes the frequency of repeated purchases that lead to consumptive behavior. This study aims to describe the consumptive behavior that occurs on Twitter related to the phenomenon of photocard collection. Theoretical reviews used in this study are mass communication, new media, social media, uses and gratification theory, and consumptive behavior. To explore this phenomenon researcher used qualitative research approaches and phenomenological methods. Data were collection from in-depth interviews with four informants, participant observation and literature study. The results obtained indicate that Twitter is actively chosen as a medium for meeting the information needs of Photocard collection. Still, the impact of using Twitter has both positive and negative sides. Then, the motivation in doing the collection is based on the fulfillment of self-satisfaction that forms consumptive behavior.Industri hiburan sangat diminati semua kalangan, tak terkecuali negara Korea Selatan yang mampu membawa K-Pop ke kancah dunia. Kesuksesan K-Pop mencetak banyak penggemar di berbagai belahan dunia, termasuk Indonesia. K-Pop dapat menjadikan penggemar sebagai bagian dari konsumen atau pelanggan yang dengan setia membeli hasil produk musiknya. Dalam beberapa tahun terakhir fenomena yang sedang digandrungi oleh penggemar K-Pop adalah koleksi Photocard yang merupakan gambar swafoto idola yang berbentuk kartu dan biasanya berada di dalam album sebagai bonus. Media sosial Twitter dimanfaatkan penggemar K-Pop sebagai pemenuhan informasi atas trend koleksi ini. Memiliki banyak koleksi Photocard menyebabkan frekuensi pembelian secara berulang yang menimbulkan perilaku konsumtif. Tujuan penelitian ini adalah untuk mendeskripsikan perilaku konsumtif yang terjadi di Twitter terkait fenomena koleksi Photocard. Dalam pembahasannya, menggunakan komunikasi massa, new media, media sosial, teori uses and gratification, dan perilaku konsumtif. Untuk mendalami fenomena ini digunakan pendekatan penelitian kualitatif dan metode fenomenologi. Pengumpulan data diperoleh dari wawancara mendalam dengan empat informan, observasi partisipan dan studi kepustakaan. Hasil yang didapatkan menunjukkan bahwa Twitter dipilih secara aktif sebagai media pemenuhan kebutuhan informasi koleksi Photocard, namun dampak penggunaan Twitter memiliki sisi positif dan negatif. Kemudian, motivasi dalam melakukan koleksi didasari pemenuhan kepuasan diri yang membentuk perilaku konsumtif.